Desnitrificação autotrófica de efluente avícola em reator de leito fixo de calcário dolomítico e enxofre elementar - Model, Adriana Neres de Lima (2016)
Nitrification associated to autotrophic denitrification, up from an elemental sulfur as an electron donor, can be an adequate option during the post-treatment of anaerobic effluent, which contains ammoniacal nitrogen that should be nitrified, and whose low carbon concentrations (C/N<5) make heterotrophic denitrification difficult. Due to the alkalinity consumption in both processes, lime materials can be applied as alkalizing to ensure the nitrogen removal efficiencies. Therefore, based on this finding, this research has proposed nitrification application followed by autotrophic denitrification in a single reactor containing elemental sulfur and dolomitic limestone to remove nitrogen from an anaerobic effluent from a cold storage from poultry industry. Thus, this study was divided into three steps due to some gaps in literature on the application of autotrophic denitrification up from elemental sulfur in real effluents. In the first step, the performance of autotrophic denitrification was evaluated in four anoxic fixed-bed reactors of elemental sulfur and dolomitic lime at 4:0, 3:1, 1:1 and 1:3 ratios. The reactors were submitted to constant nitrogen feed load (0.114 kg N m³ -1 d-1) under five initial alkalinity conditions (1,000, 800, 600, 400 and 200 mg CaCO3 L-1). The reactors showed similar behavior under those five evaluated experimental conditions. The greatest denitrification efficiencies (from 84.8 to 94.9%) were observed in the first three conditions, whose denitrification rate was 0.102 ± 0.002 kg NOx m³ -1 d-1 and apparent consumption of alkalinity superior to 244.8 mg CaCO3 L-1. Denitrification efficiencies tended to decrease due to the decrease in the initial concentration of alkalinity up from the third experimental condition (600 mg CaCO3 L-1) due to an excessive consumption and inadequate increase of alkalinity (< 180 mg CaCO3 L-1) from dolomitic limestone. During the second step, the anoxic reactor with bed composition (1: 3 ratio), whose initial alkalinity condition was 600 mg CaCO3 L-1, operated at 14, 10 and 6 h HRT. The reactor showed denitrification efficiencies of 94.4 ± 2.0; 94.9 ± 2; 71.1 ± 7.8% as well as denitrification rates of 0.115 ± 0.007; 0.164 ± 0.007 and 0.217 ± 0.025 kg NOx m³ -1 d-1 for HDT of 14, 10 and 6 hours, respectively. At the sixth hour-HRT, the applied overload and limited mass transfer may have contributed to performance decrease into the reactor due to the accumulation of gases in the bed. The third step approached about feeding strategies with mixing ammonified as well as nitrified one in different rates 1:3 (E1), 1:1 (E2) and 3:1 (E3) in anoxic-aerobic reactor of fixed bed with elemental sulfur: dolomitic limestone 1: 3, under 1,000 mg CaCO3 L-1 initial condition of alkalinity. The reactor presented some efficiencies of ammoniacal and total nitrogen removal of 67.3 ± 6.4 and 64.2 ± 6.3% for E1 condition, 63.4 ± 6.4 and 53.1 ± 7.1% for E2 and 14.2 ± 4.4 and 33.8 ± 1.7% for E3. The generation of hydrogen sulfide mainly from sulfur imbalance effect in anoxic compartment may have contributed to a partial inhibition of nitrifying bacteria. The difficulty in keeping the nitrification process was characterized as a limiting factor during nitrogen removal. Low total nitrogen removal efficiencies have implied that nitrification followed by autotrophic denitrification from elemental sulfur in a single reactor was inadequate to remove nitrogenous compounds of anaerobic effluent from a cold storage from poultry industry